ANALISIS SWOT DALAM PENENTUAN BOBOT KRITERIA PADA PEMILIHAN STRATEGI PEMASARAN MENGGUNAKAN ANALYTIC NETWORK PROCESS - Dwi Safiroh Utsalina; Liduina Asih Primandari (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
Decision Support System provides recommendations to stakeholders in making decisions,in order to carry out the management function of the organization (university). Marketing within the university carries out one of the main functions of management, namely Planning. Planning is taken to win the competition (to get new students). An increasing number of new students can be obtained with various marketing strategies as an alternative. However, not all marketing strategies are planned to be implemented in one student admission period,for this reason, a DSS approach is needed that is supported by several criteria so that it is expected to avoid stakeholders in determining subjective marketing strategies. Based on the predetermined criteria, it is necessary to determine the weight for each criterion, generally there are several ways to determine the weight of the criteria. SWOT analysis is one of the approaches used to obtain the weight of the importance of the criteria for alternatives. By using SWOT, it can provide an overview of the organization obtained, After determining the weight value of the organizational description (in this case the university) then the weight value obtained is calculated by ANP. The ANP method as an MCDM method is an extension of AHP with the concept of network construction, providing dependence between the components of the SPK, from criteria to sub-criteria, the dependence of criteria on alternatives and vice versa. Determined by determining the criteria, sub-criteria, alternatives, the weight of each component, the weight of the criteria written in a pairwise comparison to produce a supermatrix. The results of the study indicate that the SWOT can increase the objectivity of the process of determining the weight of the criteria in decisions which is indicated by an increase in the preference value of 19.3%